A temporal assessment of flooding fatalities in Pakistan (1950–2012). Issue 1 (2nd December 2013) - Paulikas, M.J.; Rahman, M.K.
Abstract Pakistan is a developing nation that has historically been subjected to high flooding fatality events due to its socioeconomic characteristics, population geography, and landscape attributes. Flooding in Pakistan has historically resulted from heavy rain events or periodic landfalling tropical cyclones that have afflicted the nation throughout its history. This study aggregates flooding events in Pakistan over a 62‐year period to identify peak years and seasonal cycles of when flood‐related fatalities have historically been highest in the nation. Seasonally, Pakistan is especially prone to flood disasters during the summer monsoon months, and also during the months of November and December, when tropical cyclone activity periodically impacts the nation. Some of the earlier flooding events have not been well documented with respect to specific months or dates of occurrence, and have therefore been excluded from the seasonal analysis portion of the study. Over the past 60 years, exceptionally high numbers of flood‐related fatalities occurred in the years 1950, 1965, and 2010; peak fatality flood years are mostly attributed to single catastrophic events caused primarily by large‐scale river floods or landfalling tropical cyclones.